An Improved Fuzzy Parallel Distributed –Like Controller for Multi-Input Multi-Output Twin Rotor System - Mahmoud, Thair Sh. (2009)
Twin Rotor Multi Input Multi Output (MIMO) System (TRMS) is a laboratory set-up design for which it has been used for control experiments, control theories developments, and applications of the autonomous helicopter. Fuzzy Logic Control (FLC) has been widely used with different control schemes to cope with control objectives of TRMS. In this work, Self Tuning Fuzzy PD-like Controller (STFPDC) is proposed to make the response of FLC more robust to the interactions and the non-linearity of the process in terms of less rising time, settling time and overshoot. Adaptive Neuro Fuzzy Inference System (ANFIS) based Fuzzy Subtractive Clustering Method (FSCM) was used to remodel the proposed STFPDC to achieve the control objectives on TRMS with less number of rules. MATLAB/SIMULINK was involved to achieve the simulations in this work. The results showed the proposed controller could simplify the STFPDC to reduce the number of rules from 392 to 73, which is even less than the original FLC that has 196 rules. The conclusion of this work is improving FLC response by using STFPDC and reducing the number of rules used to achieve this improvement by using ANFIS based on FSCM modeling. For future works, it is recommended to develop an optimization algorithm which achieves best selection for the range of influence which gives best response with less number of rules.